Manipulative Effect in Russian and Chinese Medical Commercial Advertising Texts: Linguistic and Culturological Aspect - T. Gong (Научный диалог)
The question of national-cultural conditioning of manipulative influence in Russian and Chinese medical commercial advertising texts are considered. A model of speech manipulative strategy in the advertising text is considered as the interaction of the main strategies: cognitive, prescriptive, emotive and accessory aesthetic. The novelty of the research consists in the following. (1) The author notes cultural differences between the Russian and Chinese texts when implementing manipulative influence, due to ethno-speech bans of Chinese linguistic culture, and at the same time states a significant coincidence of the communicative speech techniques in the Russian and Chinese advertising texts. (2) The notion of “manipulative effect” is clarified. The author sets out his own understanding of the interaction between the author of manipulating text and its recipient. Methods of multidimensional comparative linguistic and cultural studies are improved. The relevance of the work is based primarily on the relevance of the results of cross-cultural communicative studies, including advertising, closely related to the development of international business communication. The results of the study are significant for the teaching of stylistics of the Russian language and practical Russian language in foreign (Chinese) audience, as well as in the training of specialists in advertising and intercultural communication.